The Fatty Acid Composition and the MTT-Cytotoxicity Test of Commercially Available Commiphora Gileadensis Balsam Oil - Arzu Özgen (Health and Technology Journal (HTechJ), 2024)
Commiphora gileadensis, an aromatic plant, is traditionally used in Middle Eastern countries to prevent pain and inflammation. Fatty acid composition, peroxide number and free fatty acidity analyzes of commercially available C. gileadensis balsam oil and investigation of its effect on cell viability. Commercially available C. gileadensis balsam oil fatty acid composition, peroxide number and free fatty acidity values were determined by the IUPAC IID19 method, and MTT cell viability tests were performed on L929 fibroblast and HeLa (human epithelial cervical carcinoma) cell lines. Commercially available C. gileadensis balsam oil did not exert cytotoxic effects on both L929 fibroblast and HeLa (human epithelial cervical carcinoma) cell lines and promoted the growth of cell lines.  Due to its growth promoting feature on L929 fibroblast cells, which is a healthy cell line, this material can be used as a cell culture medium additive.